Cervical cancer and genital prolapse - Zuckermann, Conrado (2015)
It is considered important and very worthwhile to examine the association of cervical cancer and genital prolapse. The biopsy of cervical lesions (ulcer or other) if prolapse, allow to affirm or deny cancerization. It states that the most important condition is one in which invasive cervical cancer and vaginal prolapse uterus full meets. The existence of cancer in situ and prolapse is interesting and provides a viewing of this association. If prolapse cancer in situ and as indicated is usually total hysterectomy and plastic correction, all vaginally. In the cervical invasive cancer and prolapse, the behavior can be widely extirpadora radiotherapy or surgical. If surgery is decided, the route may be abdominal (linfadenohisterectomía and partial colpectomía) and complementary perineorrhaphy, or vaginal (wide hysterectomy) accompanied, followed or preceded by iliac-pelvic lymphadenectomy. Each observation of invasive cervical cancer and genital prolapse, and therapeutic merits careful study of radical tendency, if the cancerológica stage allows. The therapeutic decision will be made based on the general, functional, regional and local conditions of the patient and cervical cancer.